Experimental and ab initio Computational Studies on Dimethyl-(4-{4-(3-methyl-3-phenyl-cyclobutyl)-thiazol-2-yl]-hydrazonomethyl}-phenyl)-amine - Yuksektepe, Cigdem; Saracoglu, Hanife; Caliskan, Nezihe; Yilmaz, Ibrahim; Cukurovali, Alaaddin (Wiley-V C H Verlag Gmbh, 2010)
A new hydrazone derivative compound has been synthesized and characterized by IR, H-1-NMR, C-13-NMR and UV-vis. spectroscopy techniques, elemental analysis and single-crystal X-ray diffraction (XRD). The new compound crystallizes in monoclinic space group C2/c. In addition to the crystal structure from X-ray experiment, the molecular geometry, vibrational frequencies and frontier molecular orbitals analysis of the title compound in the ground state have been calculated by using the HF/6-31G(d, p), B3LYP/6-311 G(d, p) and B3LYP/6-31G(d, p) methods. The computed vibrational frequencies are used to determine the types of molecular motions associated with each of the observed experimental bands. To determine conformational flexibility, molecular energy profile of (1) was obtained by semi-empirical (AMI) calculation with respect to a selected degree of torsional freedom, which was varied from -180 degrees to +180 degrees in steps of 10 degrees. Molecular electrostatic potential of the compound was also performed by the theoretical method.
Keywords: Synthesis; Crystal structure; Vibrational frequency; DFT